Biochemical and cellular basis of oxidative stress: Implications for disease onset - Karl Aramouni (17746956) (2023)
Cellular oxidation–reduction (redox) systems, which encompass pro‐ and antioxidant molecules, are integral components of a plethora of essential cellular processes. Any dysregulation of these systems can cause molecular imbalances between the pro‐ and antioxidant moieties, leading to a state of oxidative stress. Long‐lasting oxidative stress can manifest clinically as a variety of chronic illnesses including cancers, neurodegenerative disorders, cardiovascular disease, and metabolic diseases like diabetes. As such, this review investigates the impact of oxidative stress on the human body with emphasis on the underlying oxidants, mechanisms, and pathways. It also discusses the available antioxidant defense mechanisms. The cellular monitoring and regulatory systems that ensure a balanced oxidative cellular environment are detailed. We critically discuss the notion of oxidants as a double‐edged sword, being signaling messengers at low physiological concentrations but causative agents of oxidative stress when overproduced. In this regard, the review also presents strategies employed by oxidants including redox signaling and activation of transcriptional programs such as those mediated by the Nrf2/Keap1 and NFk signaling. Likewise, redox molecular switches of peroxiredoxin and DJ‐1 and the proteins they regulate are presented. The review concludes that a thorough comprehension of cellular redox systems is essential to develop the evolving field of redox medicine. Other Information Published in: Journal of Cellular Physiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jcp.31071